Probiotic potential of Lactobacillus salivarius in animals of zootechnical interest - Rondón, Ana; Rodríguez, Marlén; Milian, Grethel; Beruvides, A. (Cuban Journal of Agricultural Science, 2020)
Probiotics are living microorganisms that, when consumed in adequate amounts, confer benefits to host health. Lactic acid bacteria are the most widely used, especially those of Lactobacillus genus. One of the species of this genus is Lactobacillus salivarius, capable of colonizing the digestive tract of humans and animals. It resists gastric barriers of acid pH and bile, and produces antimicrobial substances, such as organic acids and bacteriocins that inhibit different pathogenic microorganisms. This bacterium attaches to epithelial cells and stimulates the immune system. For these reasons, there is a lot of research aimed to evaluating the effect of Lactobacillus salivarius in monocultures or multistrains, on microbiological, physiological, productive and health indicators in animals of zootechnical interest. There is evidence of the results of the selection process of strains from the digestive tract of animals, in which they are candidates for their in vitro and in vivo probiotic activity. This review has the objective of evaluating the probiotic potential of Lactobacillus salivarius and its effect on poultry, pig farming and calf rearing. In addition, some future considerations are recommended for its use as a probiotic additive in animal production. Key words: probiotics, Lactobacillus salivarius, poultry, pigs, calves